A taxonomic review of the parasitoid wasp genera Furcidentia Zettel and Pseudophanerotoma Zettel (Hymenoptera: Braconidae: Cheloninae) from the Neotropics with the description of four new species - Kittel, Rebecca N. (Zootaxa, 2018)
Furcidentia Zettel, 1990 (Braconidae: Cheloninae) from the New World has been recently recognised as a genus separate from Pseudophanerotoma Zettel, 1990. Previously known from three species, three additional new species of Furcidentia are described here from the Neotropical region: F. jenningsi sp. nov. (French Guiana), F. llama sp. nov. (Guatemala), and F. tikalensis sp. nov. (Guatemala). The species F. clypeata Zettel (Ecuador) comb. nov., F. pulchra Zettel (Costa Rica) comb. nov., and F. sharkeyi Zettel (Ecuador) comb. nov. are transferred to Furcidentia. Additionally, one new species of Pseudophanerotoma is described: P. austini sp. nov. (Guatemala), while P. paranaensis (Costa Lima) (Brazil) and P. thapsina (Walley) (Texas, USA) are redescribed and are here recorded from French Guiana for the first time, thus considerably expanding their known distribution. Redescriptions include the description of the male of P. thapsina (Walley) for the first time and of the female of P. paranaensis (Costa Lima). Identification keys to the Neotropical genera of Phanerotomini and the species of Furcidentia and Pseudophanerotoma are provided.